2017
DOI: 10.17116/otorino201782284-89
|View full text |Cite
|
Sign up to set email alerts
|

Acute otitis media in the children: etiology and the problems of antibacterial therapy

Abstract: The objective of the present review was to summarize the currently available literature data on etiology of acute otitis media in the children, the role of biofilms in the development of this pathology, and sensitivity of its principal causative factors to various antibiotic medications. The secondary objective was to elaborate the practical guidelines for the prevention of acute otitis media in the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…According to the gender, our study demonstrated that the incidence of CSOM in male were more than female as (53.7%) and (46.3%), respectively, table ( 2). found the opposite, they reported that the infection percentage in female were more than male.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…According to the gender, our study demonstrated that the incidence of CSOM in male were more than female as (53.7%) and (46.3%), respectively, table ( 2). found the opposite, they reported that the infection percentage in female were more than male.…”
Section: Resultsmentioning
confidence: 57%
“…Otitis media (OM) is an infection of the middle ear that affects patients, children, and outpatients who use antibiotics randomly (Meherali et al, 2019). OM can be connected with consequences including hearing loss, recurrent acute otitis media, persistence of middle ear effusion, mastoiditis, and chronic otitis media (Protasova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It can be caused by either bacteria, such as Streptococcus pneumoniae and Haemophilus influenza , or by viruses like respiratory syncytial virus (RSV), coronaviruses, influenza viruses, and adenoviruses. 6,7 Complications such as mastoiditis and cholesteatoma, meningitis, or other intracranial complications may occur but are rare. 8 Because OM is an infectious disease, the policy and environmental efforts aimed at preventing the COVID-19 pandemic that can reduce viral or bacterial spread may affect OM prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Otitis media (OM) is an infection of the middle ear that affects patients, adult and children, who abuse and overuse of antibiotics [1]. The complications of OM infection may lead to hearing loss, recurrent acute otitis media, persistence of middle ear effusion, mastoiditis, and chronic otitis media [2]. The acute cases of otitis media (AOM) is characterized by the accumulation of fluids in the middle ear and the presence of symptoms of the middle ear infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…P-ISSN:Figure 1: Antibacterial activity of ciprofloxacin against bacterial isolatesRegarding the CFS of mixed lactobacilli, it was found to be 25% against P. mirabilis which inhibited 91.4%, while was 50% against k. pneumoniae, P. aeruginosa, and S. aureus caused growth inhibition 93.3%, 90.5%, and 90.5%, respectively, figure(2).P-ISSN:…”
mentioning
confidence: 99%